Environmental, Social dan Governance (ESG) dan Kinerja Keuangan Perusahaan Publik di Indonesia - Angela Merici Minggu; Jusuf Aboladaka; Godlief Fredrik Neonufa (Owner : Riset dan Jurnal Akuntansi, 2023)
Companies have an important responsibility to contribute to pursuing and achieving the Sustainable Development Goals (SDGs) introduced by the United Nations. The company's approach used as an opportunity to contribute is engagement in practices that cover environmental, social and governance (ESG) aspects. Stakeholders will pay attention to companies that use the ESG strategy as part of the company's business strategy. This will certainly have an impact on increasing the value of the company. Changes in company value are driven by the good financial performance of the company. ESG practices are expected to receive a positive response from stakeholders so that they are considered as an important strategy in achieving the company's business continuity. Therefore, this study investigates the relationship between environmental, social and governance (ESG) practices and the performance of financial firms. The sample in this study was obtained using a purposive sampling technique. The sample was selected from a population of public companies listed on the Indonesia Stock Exchange in the 2010-2019 time period. The sample data obtained were grouped according to each of the research variables to be tested, namely environmental, social, governance, and Tobin's Q. Furthermore, hypothesis testing was carried out using the panel data regression statistical test approach with the help of SPSS 22 software. The results of the research show that environmental, social, and government variables affect the company's financial performance individually.